2007
DOI: 10.4049/jimmunol.178.7.4147
|View full text |Cite
|
Sign up to set email alerts
|

The Blood Contains Multiple Distinct Progenitor Populations with Clonogenic B and T Lineage Potential

Abstract: The thymus is seeded by bone marrow-derived progenitors that circulate in the blood. Multiple cell types can be found in the thymus early after i.v. administration or in steady state, but most fail to satisfy the known characteristics of true T progenitors. Cells that do conform to classical definitions retain multilineage potential, but surprisingly, cannot make B cells. Because acquisition of the T lineage fate among noncommitted progenitors is a lengthy process, the absence of B cell potential in early thym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Our phenotypic analysis of blood-derived precursor populations is in agreement with previous work, indicating that most BM-derived T-cell precursors such as MPPs and CLPs as well as CLP-like cells have been found in blood. 27 However, CLP-2 cells remain yet to be identified above the limit of detection and a direct BM-resident precursor of CTPs remains elusive. 11 Comparison of phenotypically matched precursors in BM and blood revealed virtually no differences with respect to lineage potential and differentiation kinetics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our phenotypic analysis of blood-derived precursor populations is in agreement with previous work, indicating that most BM-derived T-cell precursors such as MPPs and CLPs as well as CLP-like cells have been found in blood. 27 However, CLP-2 cells remain yet to be identified above the limit of detection and a direct BM-resident precursor of CTPs remains elusive. 11 Comparison of phenotypically matched precursors in BM and blood revealed virtually no differences with respect to lineage potential and differentiation kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Umland et al identified a CD127 ÏȘ/lo population with otherwise CLP-like characteristics that would not be included in our depletion approach and may constitute a physiologic T-lineage precursor. 27 To reach the thymus, precursors must enter the circulation. Our study revealed that in both BM and blood multiple progenitor populations capable of thymus seeding and T-lineage reconstitution exist.…”
Section: Discussionmentioning
confidence: 99%
“…The LMPP, the ELP and the CLP are detectable in peripheral blood, whereas the CLP-2 has not been found in the blood (Schwarz and Bhandoola, 2004;Perry et al, 2006;Krueger and von Boehmer, 2007;Umland et al, 2007). Recently, a novel T-lineage-committed progenitor subset presumably downstream of the CLP-2 was found in adult murine blood.…”
Section: Developmental Pathways In Murine Hematopoiesismentioning
confidence: 99%
“…In transplantation settings, it has been shown that different progenitors can home to the thymus and generate T cells [1][2][3][4][5][6][7][8][9]. However, under physiological conditions the role of each of these progenitors is still unclear.…”
Section: Introductionmentioning
confidence: 99%